Nutritional profile before and after hypotermal and mineral water consumption in hypertensive individuals - Oliveira, Isadora Lopes de; Vilela, Luiza Amaral; Manochio-Pina, Marina Garcia; Santos, Daniel dos; Castro, Eliane Aparecida [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2021)
Introduction: The availability of different mineral waters, some with indications of therapeutic properties, makes it necessary to investigate their interaction with nutritional habits. Objective: To analyze the nutritional profile before and after 10 days of ingestion of hypothermic water enriched with minerals in hypertensive individuals. Materials and Methods: Fifteen hypertensive adults (73% women), 47.9 +/- 7.7 years, were randomly divided between control group (CG; n=7) and experimental group (EG; n=8). For 10 days, the individuals ingested hypothermic water enriched with minerals or placebo mineral water. The amount was established in 75% of: 1500ml + 20ml * body weight. Participants were instructed to maintain their eating habits. Macro and micronutrients were calculated using the DietPro (R) 5i software with the information obtained from the 24-hour recalls applied before and after mineral water consumption. Results: For both groups, there were no significant differences between the macro and micronutrients of the diet evaluated before and after the intervention. When CG and EG were compared in the pre and post separately, there were also no differences between them, except for fiber where the amount consumed by the CG in the post intervention was greater than that consumed by the EG (p=0.034). There was a trend towards an association between caloric intake and body weight at the beginning of the intervention (p=0.071). Conclusion: There were no changes in relation to diet before and after 10 days of ingestion of hypothermal water enriched with minerals, suggesting that the consumption of this type of water does not interfere in the patterns of eating behavior. However, studies involving a larger number of participants and a longer consumption period are necessary.
Keywords: Hypertension; Energy intake; Fluid intake; Nutrients